The European Law Enforcement Agencies in a space of liberty, security and justice (2010)
Since the coming into force of the Maastricht Treaty, the European Community (EC) has expanded its integration policy, after the strengthening of the socio-economic and monetary integration, to crucial aspects of the justice and home affairs policies. Eur